2018
DOI: 10.1159/000490688
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Action of Sitagliptin and Linagliptin in Doxorubicin Nephropathy

Abstract: Background/Aims: Dipeptidyl peptidase-4 (DPP4) inhibitors are known to have a protective effect on diabetic kidney disease, possibly via reduction of oxidative stress and inflammation in the kidney. However, whether these potential mechanisms play a role in non-diabetic proteinuric kidney diseases is not clear. Methods: Two different animal experiments were carried out using sitagliptin and linagliptin for DPP4 inhibition. In each experiment, male Sprague-Dawley rats were uninephrectomized and randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 49 publications
(45 reference statements)
2
27
0
Order By: Relevance
“…In obese DIO mice, it is well documented that systemic dpp4 inhibitors exert anti-inflammatory properties [23, 24]. In our study with obese and hyperglycemic db/db mice, we were able to confirm that systemic dpp4 inhibition has anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 79%
“…In obese DIO mice, it is well documented that systemic dpp4 inhibitors exert anti-inflammatory properties [23, 24]. In our study with obese and hyperglycemic db/db mice, we were able to confirm that systemic dpp4 inhibition has anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 79%
“…Saxagliptin was previously shown to inhibit the AngII-induced activation of a range of cardiac proinflammatory/profibrotic signaling intermediates, including interleukin 18 (IL-18), interleukin 17A (IL-17A), nuclear transcription factor-κB (NF-κB), and TLR4 (39). Interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) have been positively correlated with blood pressure (40, 41), and the inhibition of DPP-4 has been shown to down-regulate the expression of IL-6 and TNF-α (36, 42, 43). In contrast, Tinsley et al found that interleukin 10 (IL-10), released by Treg cells, has beneficial effects in terms of reducing inflammation, ameliorating endothelial function, and lowering BP in hypertensive pregnant rats (44).…”
Section: Dpp-4 Inhibitors and Bp Regulation: Potential Mechanismsmentioning
confidence: 99%
“…Moreover, many studies were performed to explore the deeper mechanism. For example, Jo et al showed that DPP-4i can restrain the activity of the nod-like receptor protein 3 (NLRP3) inflammasome by alleviating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2-associated oxidative stress (43). Hu et al further showed that the treatment of vascular endothelial cells with sitagliptin could inhibit the TNF-induced expression of vascular cell adhesion mole 1 (VCAM-1) mRNA (54).…”
Section: Dpp-4 Inhibitors and Bp Regulation: Potential Mechanismsmentioning
confidence: 99%
“…Currently, the anti‐inflammatory activity of Sita has been shown in various kinds of organ damage, for example, cardiovascular, hepatocellular and renal damage . Prominently, Sita has demonstrated nephroprotective action in experimental initiated nephropathy by means of regulation of lipid metabolism, oxidative stress (OS), and inflammatory mediators …”
Section: Introductionmentioning
confidence: 99%